Algerian Language and Identity: Study and Analysis of Audiovisual Text and Subtitling - Kerras, Nassima; Baya E, Moulay (Dirasat: Human and Social Sciences, 2020)
The study consists of analyzing the Algerian language, also referred to as the Algerian dialect, in order to explore its use within Algerian society. The Algerian dialect is a national language which is seldom studied, although it is the language predominantly used in everyday life (Chachou, 2008; Kerras and Baya, 2017, 2016; Ibrahimi, 2004, etc.). The objective of our study is to demonstrate, once again, that the Algerian dialect is a language in its own right (Kerras and Baya, 2018), as each country has the right and the duty to use their mother tongue not only in domestic affairs but also in education so as to avoid discrimination and social exclusion (Amorós Negre, 2014). For these reasons, a complementary study is carried out in order to study the use of the Algerian language in audiovisual contexts, with a particular focus on subtitles.